2021
DOI: 10.3390/ijms22168797
|View full text |Cite
|
Sign up to set email alerts
|

Organic Anion Transporting Polypeptide 1B1 Is a Potential Reporter for Dual MR and Optical Imaging

Abstract: Membrane proteins responsible for transporting magnetic resonance (MR) and fluorescent contrast agents are of particular importance because they are potential reporter proteins in noninvasive molecular imaging. Gadobenate dimeglumine (Gd-BOPTA), a liver-specific MR contrast agent, has been used globally for more than 10 years. However, the corresponding molecular transportation mechanism has not been validated. We previously reported that the organic anion transporting polypeptide (OATP) 1B3 has an uptake capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Because TCDD can cross the placental barrier ( 39 ), the direct effect of TCDD on the thymus in F1 generation can be expected, however, whether the toxic effects can be preserved even in the F2 and subsequent generations remains an intriguing possibility. To that end, several studies have focused on the transgenerational effects of TCDD on the reproductive functions [reviewed in ( 40 , 41 )] and shown that F1 mice exposed to TCDD in utero exhibit reduced fertility and an increased incidence of premature birth, an effect that is maintained for the next three generations ( 42 ). Similarly, female C57BL/6 mice (F1), exposed in utero to TCDD (10 μg/kg) by oral gavage at gestational day (GD) 15 exhibited endometriosis-like uterine phenotype in adult life ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because TCDD can cross the placental barrier ( 39 ), the direct effect of TCDD on the thymus in F1 generation can be expected, however, whether the toxic effects can be preserved even in the F2 and subsequent generations remains an intriguing possibility. To that end, several studies have focused on the transgenerational effects of TCDD on the reproductive functions [reviewed in ( 40 , 41 )] and shown that F1 mice exposed to TCDD in utero exhibit reduced fertility and an increased incidence of premature birth, an effect that is maintained for the next three generations ( 42 ). Similarly, female C57BL/6 mice (F1), exposed in utero to TCDD (10 μg/kg) by oral gavage at gestational day (GD) 15 exhibited endometriosis-like uterine phenotype in adult life ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…ICG is a hydrophilic tricarbocyanine dye (Figure 1C), which after intravenous injection, rapidly binds to plasma proteins and is secreted by the liver in bile, due to hepatobiliary transporters, such as OATPs [80] and MDR1 (gene ABCB1) (Figure 2) [81]. ICG becomes fluorescent when excited by a flash of light in the near-infrared (NIR) spectrum, which can be detected extracorporeally.…”
Section: Icg Testmentioning
confidence: 99%
“…Most recently human OATPs (OATP1B3 and OATP1B1) have been expressed in cancer cells to perform longitudinal, 3D tracking of engineered cells in vivo (Figure ). …”
Section: Introductionmentioning
confidence: 99%